Gyozarap - Alapan, Aaron Nethaniel D. Billona, Jomarie A. Carino, Mark Ryan R. Gonzales, Altheza Lanna B. Inocelda, Realyn S. Martin, Jiliah L. Secretario, Darel Joyce H. 4 0 16; 5
u
Feasibility Study : (BSBA major in Operations Managment) - Pamantasan g Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2